Consumo de alcohol y su repercusión en la disfunción familiar de los adolescentes del sector Tierras Coloradas de la ciudad de Loja, en el año 2015 - Zabala Gálvez, Fabián Alexander (2016)
Alcoholism is a social problem that affects adolescents and the family, so this study of qualitative and quantitative cross - type is performed, by the CID “Questionnaire Diagnostic Indicators " and CAGE screening test to determine the relationship between alcohol consumption and its impact with family dysfunction in adolescents of the population of Tierras Coloradas of city Loja in 2015. The percentage of social consumers it was 40.7% and the alcohol dependent 5%. Was evalued family function of individuals in the respective group , showing that there is a greater proportion of mild family dysfunction, followed by a good function and moderate dysfunction, severe dysfunction in a smaller proportion. By relating the results of such consumers, and family dysfunction was obtained: social consumption, with 25.4% of good function, 50.8% with mild dysfunction, 22% moderate and 1.7% dysfunction severe dysfunction. The risk consumption presented 40% with good function, mild dysfunction 44.4%, moderate dysfunction 15,6%, and there is no severe. Harmful use with 25,6% good function, 37,9% with mild dysfunction, 31% dysfunction moderate and 3.4% severe dysfunction. The group having alcohol dependence has a good function 28.6%, 42.9% mild dysfunction and 28.6% dysfunction severe, which support the conclusion that there is no direct relationship between the two variables and therefore that at alcohol consumption by adolescents there are other factors to be considered more of family functionality. Keywords Alcohol, CID, CAGE, Family Function